1995
DOI: 10.1007/bf00212498
|View full text |Cite
|
Sign up to set email alerts
|

Environmental polychlorinated biphenyls: Acute toxicity of landfill soil extract to female prepubertal rats

Abstract: Subsurface soil from a National Priorities List landfill containing about 2.5% polychlorinated biphenyls (PCBs) was extracted and the extract cleaned by Florisil slurry and alumina column chromatography. The refined extract contained 48 mg/mL PCB, mainly trichlorobiphenyls and tetrachlorobiphenyls, traces of polychlorinated naphthalenes, 125 micrograms/mL 2,2-bis-p-chlorophenyl-1,1-dichloroethylene (DDE), and low levels of chlorinated dibenzofurans. The refined extract was dissolved in corn oil and administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Four 1-ml aliquots of soil extract were chromatographed separately over the adsorbent, eluting with 20 ml of hexane (Fraction 1); two subsequent 10-ml eluates (Fractions 2 and 3) were retained separately for analysis only. Gas chromatography with electron capture detection (GC-ECD) on a 60-m DB-5 capillary column, as described in Hansen et al (1995, was conducted for the initial and charcoal-refined soil extracts to determine the amount and profile of PCBs recovered and lost PCDDS and PCDFs could not be detected by these methods. The basic proportions of the major PCB components were not changed (Fig.…”
Section: Charcoal-alumina Column Chromatographymentioning
confidence: 99%
“…Four 1-ml aliquots of soil extract were chromatographed separately over the adsorbent, eluting with 20 ml of hexane (Fraction 1); two subsequent 10-ml eluates (Fractions 2 and 3) were retained separately for analysis only. Gas chromatography with electron capture detection (GC-ECD) on a 60-m DB-5 capillary column, as described in Hansen et al (1995, was conducted for the initial and charcoal-refined soil extracts to determine the amount and profile of PCBs recovered and lost PCDDS and PCDFs could not be detected by these methods. The basic proportions of the major PCB components were not changed (Fig.…”
Section: Charcoal-alumina Column Chromatographymentioning
confidence: 99%
“…Hansen et al, observed no toxic effects of PCBs on the kidney in weanling female rats. 20 Induction of cytochrome P450 enzymes by PCBs both in kidney and liver has been shown. 21,22 Histological alterations in kidney were observed after administration of A1254 at 25 mg/kg for a period of 10 and 15 weeks.…”
Section: Introductionmentioning
confidence: 98%
“…After acute (2-day) exposures, thyroidstimulating hormone (TSH) levels may increase up to 5-fold (38) and the thyroid follicles show typical responses (32,39) to TSH-stimulated mobilization of T4 (39)(40)(41). The follicular response (increased cell height and decreased colloid area) appears maximal at doses below those at which significant declines in serum T4 are seen (40,41).…”
Section: Selection Criteriamentioning
confidence: 99%
“…The follicular response (increased cell height and decreased colloid area) appears maximal at doses below those at which significant declines in serum T4 are seen (40,41). Mobilization of stored T4 from the thyroid follicles at doses lower than or times prior to those causing significant UDPGT induction (17,38) can cause elevations in serum T4 (17,42,43); at higher doses, declines in serum T4 are still seen at times prior to maximal UDPGT induction (17,38,42,43).…”
Section: Selection Criteriamentioning
confidence: 99%